2004
DOI: 10.1111/j.1440-1843.2004.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

COPD in Japan: the Nippon COPD Epidemiology study

Abstract: Prevalence of airflow limitation in Japan is higher than previously reported, suggesting a high degree of under-recognition of COPD. The high prevalence of smoking coupled with an aging population threatens to further increase the burden of COPD, highlighting the need for enhanced screening efforts and interventions of prevention and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
398
13
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 512 publications
(455 citation statements)
references
References 23 publications
(21 reference statements)
38
398
13
6
Order By: Relevance
“…Study II involved 1-day screening, and validated the data from study I, which was performed over 4 consecutive years. COPD prevalence on the 2 islands was similar (study I vs. II: 9.4 vs. 8.7%) and the findings were in line with that found in a previous study performed on the Japanese mainland (12). Mass screening would encourage the awareness or prevention of COPD, for example, by promoting cessation of smoking; however, the present study found that such screening does not efficiently identify true COPD patients in situations in which the quality and training of examiners is not guaranteed.…”
Section: Discussionsupporting
confidence: 91%
“…Study II involved 1-day screening, and validated the data from study I, which was performed over 4 consecutive years. COPD prevalence on the 2 islands was similar (study I vs. II: 9.4 vs. 8.7%) and the findings were in line with that found in a previous study performed on the Japanese mainland (12). Mass screening would encourage the awareness or prevention of COPD, for example, by promoting cessation of smoking; however, the present study found that such screening does not efficiently identify true COPD patients in situations in which the quality and training of examiners is not guaranteed.…”
Section: Discussionsupporting
confidence: 91%
“…The Nippon COPD Epidemiology (NICE) Study 84) reported that COPD is an increasingly important health problem in Japan with a prevalence of 8.6% in the Japa-nese population over 40 years of age. The prevalence and burden of COPD are projected to increase in the coming decades as a result of continued exposure to COPD risk factors (mainly cigarette smoke) and the aging of the Japanese population.…”
Section: Resultsmentioning
confidence: 99%
“…COPD has high prevalence and mortality, both of which are generally underestimated because many COPD patients are not diagnosed (1)(2)(3). A NICE (Nippon COPD Epidemiology) Study estimated the prevalence of COPD in Japan to be 5,300,000, but the number of patients treated yearly is only 220,000 (2).…”
Section: Spirometry Is Indispensable For the Evaluation Of Pulmonary mentioning
confidence: 99%
“…A NICE (Nippon COPD Epidemiology) Study estimated the prevalence of COPD in Japan to be 5,300,000, but the number of patients treated yearly is only 220,000 (2). Underdiagnosis is thought to result from patients being unaware of the disease until it is advanced, and also from the fact spirometry, the most important tool Division (4)(5)(6) (4)(5)(6).…”
Section: Spirometry Is Indispensable For the Evaluation Of Pulmonary mentioning
confidence: 99%